A meta-analysis of whole blood transcriptome reveals genes associated with increased neutrophil activity and T cell suppression in sepsis - T. N. Shruthi; Anbazhagan Kolandaswamy; Prabakara Somanna (Egyptian Journal of Medical Human Genetics)
Abstract Background Sepsis is a multi-organ dysfunction due to an uncontrolled host-response to pathogens, a leading cause of mortality in intensive care unit. Understanding the underlying mechanism associated with sepsis is essential for discovering biomarkers for better management and treatment. Though several genes are associated with severity of sepsis, there exists vast heterogeneity among gene expression studies. Hence our study was limited to transcriptome data derived solely from whole blood to understand the pathogenesis and immune regulation in sepsis. Methods We considered six publically available whole blood transcriptome gene expression omnibus (GEO) datasets and analyzed them using GEO2R. DESeq-R package was used to identify differentially expressed genes. Significant (p-value ≤ 0.05 and log fold change ≤ − 1.5 or ≥  + 1.5) common genes from six studies were subjected to network analysis and functional enrichment analysis to identify enriched Gene ontology (GO) terms, Kyoto Encyclopedia of Genes and Genomes pathways and hub genes. Results Gene expression data resulted in 233 differentially expressed genes (DEGs), 146 genes were up-regulated and 87 genes were down-regulated. Through network and functional enrichment analysis, 20 hub genes were found, 11 genes were up-regulated, and nine genes were down-regulated. The up-regulated genes (CD177, MMP8, ARG1, IL18R1, RETN, LTF, S100A12, S100A8, S1000A9, MMP9, and ELANE) were associated with the innate immune system and regulate neutrophil activity. Down-regulated genes (FCERIA, IL7R, CCR7, CX3CR1, CD3G, CD40LG, CD247, CD3E, and GZMK) were associated with adaptive immune response, T cell function, and antigen processing and presentation. Conclusion The GO terms, pathways, and the genes associated with increased neutrophil activity were found to be up-regulated and T cell function were down-regulated. Dysregulation of immune response, imbalance between pro-inflammatory and anti-inflammatory response, apoptosis, and anti-apoptotic genes were found to be associated with immunosuppression and increased inflammatory reaction during sepsis. The genes identified through functional analysis could be used as potential diagnostic, prognostic, and therapeutic targets for sepsis conditions.